CAMPO ARÁUZ, Lorena e APARICIO, Miguel (Orgs.). Etnografías del suicidio en América del Sur. (Anuário Antropológico, 2018)
Resenha: CAMPO ARÁUZ, Lorena & APARICIO, Miguel (orgs.). Etnografías del suicidio en América del Sur. Quito: Abya-Yala, 2017; 311 pp.